A chinese medicine formula (kunbixiao granule) for female rheumatoid arthritis: Study protocol for a double-blind, randomized, placebo-controlled trial - Wan, Yingying; Yang, Jiaxi; Ma, Tianyue; Wang, Wenqian; Wang, Haonan; Sun, Wenting; Ye, Wanting; Yang, Lin; Kou, Qiuai (Frontiers in Pharmacology, 2022)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease affecting females more than males. Clinical symptoms, disease activity and comorbidities are more severe in females. Moreover, the choice of treatment for females is limited during childbearing age due to the side effects of current drugs. Therefore, developing novel and safer drugs for females is urgently needed. Kunbixiao granules (KBXG), a Chinese medicine formula, has been applied to treat female RA patients in our center as a complementary therapy. However, there is insufficient evidence for its effect. Therefore, we aim to conduct a randomized, controlled, double-blind clinical trial to confirm the efficacy and safety of KBXG for the treatment of female RA. Methods: This study is a single-center, double-blind, randomized, parallel group, placebo-controlled clinical trial. A total of 90 female RA patients with Disease Activity Score for 28 joints (DAS28) > 3.2 will be enrolled. They will be randomly assigned to receive either KBXG or placebo for 12 weeks. The change in DAS28 based on C-reactive protein (DAS28-CRP) and the Clinical Disease Activity Index (CDAI) are the primary outcomes. The secondary outcomes include a rate of achieving 20%, 50% and 70% improvement in the American College Rheumatology criteria (ACR20, ACR50, ACR70), TCM syndrome score, visual analogue scale (VAS), average hands grip strength, the consumption of concomitant medication, Hospital Anxiety and Depression Scale (HADS), lumbar spine bone mineral density (L-BMD) and 7-joint ultrasound score (US7). Any adverse events will also be recorded. Discussion: This trial will provide evidence of KBXG in reducing disease activity, and improving clinical symptoms and quality of life of female RA patients. The long-term effects of KBXG on female RA patients still needs a further follow-up.